Instituições, organizações e empreendedorismo: práticas inovativas no campo do turismo local/regional – o caso da "Rota das Emoções" (eixo Piauí) - Mendes, Maria de Lourdes de Melo Salmito (2021)
This thesis contends that innovation, if institutionally worked and/or endeavored in tourism on the "Rota das Emoções" (Piauí axis), can generate positive impacts on local-regional culture. In this context, institutional entrepreneurship emerges as an answer to questions related to the birth of institutions in organizational fields related to changes in the current institutional logic, and the legitimation of new practices and new institutional arrangements. In this context, the aim of the study was to analyze how issues of innovation are institutionally worked and/or undertaken in tourism on the "Rota das Emoções" (Piauí axis). The innovative and original nature of this work involved the articulation of these themes as well as the empirical object – the "Route of Emotions" (Piauí axis) –, when considering organizational aspects and the field of Tourism, resulting not only in theoretical contributions, as well as practical and social. Ontologically and epistemologically, it is a constructionist and interpretive study, with a qualitative approach of descriptive-exploratory nature, portraying the organizational field of regional tourism as level of analysis, and innovative practices as unit of analysis, adopting, for this, sociological Organizational Institutionalism as theoretical lens. A case study was carried out with material from primary (semi-structured interviews, informal conversations and observation) and secondary (documents) sources, in which the empirical material was analyzed through document analysis and qualitative content analysis. Results showed the existence of several social actors and the relevance of their actions in the development of the "Route of Emotions" (Piauí axis), the importance of local-regional culture as a strongly worked aspect on in this route, which has considerable impact on innovative practices. The actions of the state – this one being more active in the beginning of the construction process of the "Route", however, absent at the time of conclusion of this study, regarding the lack of structural public policies –, SEBRAE and businessmen/entrepreneurs stand out as relevant social actors. Other findings evidenced the action of entrepreneurs and institutional entrepreneurship in the region, always seeking innovative practices, in addition to the existence of several types of institutional work of political, technical and cultural nature carried out by the actors. Finally, a temporal transition in the evolution of the "Route" was identified, in which culture is no longer individual and is based on collective action of a coopetitive character – i.e., cooperation in a competitive environment –, given that public policies still need further advances to meet the demands of the various actors in the field. In conclusion, innovation, entrepreneurship and institutional work promoted the development of the "Route of Emotions" (Piauí axis), reflected in the permanence and frequency of tourists in the region, which directly impacted the local and regional development of the region as follows: actors carried out institutional work in a cooperative and collective way, contributing to a vision of the "Route" that goes beyond the economic perspective, reaching the social dimension based on local and regional culture.